Implikasi Kebijakan Hukum Terhadap Struktur Sosial dalam Penguatan Kedaulatan Negara - Arief Fahmi Lubis (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2022)
This study examines the implications of legal policies on the social structure of village communities in rural areas of Indonesia. Using a qualitative approach based on literature review, this research analyzes how the implementation of various legal policies affects social dynamics, power relation patterns, and local institutions in rural areas. The results show that legal policies, especially those related to decentralization, agrarian reform, and recognition of indigenous communities, have resulted in significant changes in rural social structures. However, their impact varies depending on local context and community capacity in responding to changes. This study identifies transformations in local leadership, restructuring of access to resources, and shifts in traditional value systems. These findings highlight the importance of a more contextual and participatory approach in the formulation and implementation of legal policies in rural areas.